Functional consequences of calcium-dependent synapse-to-nucleus communication: focus on transcription-dependent metabolic plasticity - Hertle, Anna M.; Bading, Hilmar; Bas Orth, Carlos (Cold Spring Harbor perspectives in biology, 2020)
In the nervous system, calcium signals play a major role in the conversion of synaptic stimuli into transcriptional responses. Signal-regulated gene transcription is fundamental for a range of long-lasting adaptive brain functions that include learning and memory, structural plasticity of neurites and synapses, acquired neuroprotection, chronic pain, and addiction. In this review, we summarize the diverse mechanisms governing calcium-dependent transcriptional regulation associated with central nervous system plasticity. We focus on recent advances in the field of synapse-to-nucleus communication that include studies of the signal-regulated transcriptome in human neurons, identification of novel regulatory mechanisms such as activity-induced DNA double-strand breaks, and the identification of novel forms of activity- and transcription-dependent adaptations, in particular, metabolic plasticity. We summarize the reciprocal interactions between different kinds of neuroadaptations and highlight the emerging role of activity-regulated epigenetic modifiers in gating the inducibility of signal-regulated genes.
First published online September 30, 2019
Gesehen am 17.04.2020